Metabolism Characterization and Chemical and Plasma Stability of Casearin B and Caseargrewiin F - Oda, Fernando Bombarda [UNESP]; Carvalho, Flávio Alexandre [UNESP]; Yamamoto, Priscila Akemi; De Oliveira, Jonata Augusto [UNESP]; Peccinini, Rosângela Gonçalves [UNESP]; Zocolo, Guilherme Julião; Ribeiro, Paulo Riceli Vasconcelos; De Moraes, Natália Valadares; Dos Santos, André Gonzaga [UNESP] (Thieme, 2023)
Oral preparations of Casearia sylvestris (guacatonga) are used as antacid, analgesic, anti-inflammatory, and antiulcerogenic medicines. The clerodane diterpenes casearin B and caseargrewiin F are major active compounds in vitro and in vivo. The oral bioavailability and metabolism of casearin B and caseargrewiin F were not previously investigated. We aimed to assess the stability of casearin B and caseargrewiin F in physiological conditions and their metabolism in human liver microsomes. The compounds were identified by UHPLC-QTOF-MS/MS and quantified by validated LC-MS methods. The stability of casearin B and caseargrewiin F in physiological conditions was assessed in vitro. Both diterpenes showed a fast degradation (p < 0.05) in simulated gastric fluid. Their metabolism was not mediated by cytochrome P-450 enzymes, but the depletion was inhibited by the esterase inhibitor NaF. Both diterpenes and their dialdehydes showed a octanol/water partition coefficient in the range of 3.6 to 4.0, suggesting high permeability. Metabolism kinetic data were fitted to the Michaelis-Menten profile with K Mvalues of 61.4 and 66.4 μM and V maxvalues of 327 and 648 nmol/min/mg of protein for casearin B and caseargrewiin F, respectively. Metabolism parameters in human liver microsomes were extrapolated to predict human hepatic clearance, and suggest that caseargrewiin F and casearin B have a high hepatic extraction ratio. In conclusion, our data suggest that caseargrewiin F and casearin B present low oral bioavailability due to extensive gastric degradation and high hepatic extraction.
Keywords: Casearia sylvestris; clerodane diterpene; hepatic metabolism; IVIVE; Salicaceae